2002
DOI: 10.1038/sj.bjc.6600014
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the RNA-amplification based methods RT–PCR and NASBA for the detection of circulating tumour cells

Abstract: Increasingly, reverse transcriptase polymerase chain reaction (RT–PCR) is used to detect clinically significant tumour cells in blood or bone marrow. This may result in a redefinition of disease-free and clinical relapse. However, its clinical utility may be limited by lack of automation or reproducibility. Recent studies have suggested nucleic acid sequence-based amplification of target RNA may be more robust. In this study, nucleic acid sequence-based amplification was established to detect melanoma, colorec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 21 publications
0
11
0
1
Order By: Relevance
“…It has been reported that HPV could be the causative agent responsible for the marked increase in at least a subset of HNSCC in young adults [37]. Of course, the mere presence of HPV DNA in HNSCC does not necessarily imply causation, and for HPV-mediated malignant transformation to occur, HPV viral E6/E7 oncogenes must be expressed [29]. To address this, we looked for both HPV DNA and mRNA in 21 of 24 of the cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that HPV could be the causative agent responsible for the marked increase in at least a subset of HNSCC in young adults [37]. Of course, the mere presence of HPV DNA in HNSCC does not necessarily imply causation, and for HPV-mediated malignant transformation to occur, HPV viral E6/E7 oncogenes must be expressed [29]. To address this, we looked for both HPV DNA and mRNA in 21 of 24 of the cases.…”
Section: Discussionmentioning
confidence: 99%
“…The isothermal NASBA reaction occurs at 41°C. Thus, double-stranded DNA is not denatured and consequently is not amplified [29]. As a result, the presence of intron-exon boundaries or the inclusion of DNase digestion steps is superfluous, and contaminating HPV DNA should not affect the efficiency of the reaction or generate false-positive results.…”
Section: Detection Of Hpv 16/18 Rnamentioning
confidence: 97%
“…However the distinguishing aspect of our work implies the use of the biochemical entities (MDA and mRNA) as a potent marker of HIV infection process as well as the progression of the disease using serodiscordant heterosexual partners of black origin as subjects. Measurement of HIV mRNA is usually done using the polymerase chain reaction (RT-PCR) [44]. Detection and Measurement of cell-associated RNA species using reverse transcription and the polymerase chain reaction (RT-PCR) is not now routinely done in hospitals or commercial clinical laboratories.…”
Section: Discussionmentioning
confidence: 99%
“…Aplikasi dan pengembangan metode NASBA telah banyak dikembangkan untuk tujuan deteksi berbagai agen patogen seperti virus, bakteri, jamur, parasit, dan juga sel tumor (Burchill et al, 2002;Loens et al, 2005). Menurut Compton (1991) teknologi NASBA dapat diaplikasikan untuk penapisan jaringan makanan/food screening, diagnostik veteriner, aquakultur dan juga ilmu forensik.…”
Section: Pendahuluanunclassified